2019
DOI: 10.1029/2019pa003665
|View full text |Cite
|
Sign up to set email alerts
|

Intense Hurricane Activity Over the Past 1500 Years at South Andros Island, The Bahamas

Abstract: Hurricanes cause substantial loss of life and resources in coastal areas. Unfortunately, historical hurricane records are too short and incomplete to capture hurricane-climate interactions on multi-decadal and longer timescales. Coarse-grained, hurricane-induced deposits preserved in blue holes in the Caribbean can provide records of past hurricane activity extending back thousands of years. Here we present a high resolution record of intense hurricane events over the past 1500 years from a blue hole on South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(158 citation statements)
references
References 84 publications
7
150
1
Order By: Relevance
“…When there was more than one event in a blue hole record falling within the age uncertainties of an event from another blue hole record, we consolidated the event in the first blue hole site that was closest in age to that captured in the second site. The main difference between the new South Andros stack presented here and the solitary paleo record from blue hole AM4 featured by Wallace et al 25 is a period of increased activity in the stacked record from ~ 1600 to 1780 CE.…”
Section: Event Threshold Attribution and Frequencycontrasting
confidence: 68%
See 2 more Smart Citations
“…When there was more than one event in a blue hole record falling within the age uncertainties of an event from another blue hole record, we consolidated the event in the first blue hole site that was closest in age to that captured in the second site. The main difference between the new South Andros stack presented here and the solitary paleo record from blue hole AM4 featured by Wallace et al 25 is a period of increased activity in the stacked record from ~ 1600 to 1780 CE.…”
Section: Event Threshold Attribution and Frequencycontrasting
confidence: 68%
“…The methods of to identify the most likely intervals (i.e., event beds) where coarse-grained sedimentation substantially exceeds background sedimentary conditions were modified from Donnelly, et al 18 , Wallace, et al 25 , Lane et al 27 . First, an 11-point moving average of data excluding those with a coarse fraction value > 12% (upper 90th percentile of %D >63 µm ) was subtracted from all %D >63 µm data to establish a series of coarse sediment anomalies (CSA).…”
Section: Event Threshold Attribution and Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Sedimentary studies along the coasts of various islands and in lagoons have revealed deposits related to past hurricanes (Donnelly and Woodruff, 2007;McCloskey and Keller, 2009;Malaizé et al, 2011;Donnelly et al, 2015;Denommee et al, 2015;Wallace et al, 2019), but no paleotempestology studies have been conducted in Anguilla or Scrub Island.…”
Section: Past Hurricanes In the Lesser Antillesmentioning
confidence: 99%
“…Scrub Island sediment record brings new knowledge about variations in past hurricane activity in the Caribbean. Thus we compared this new chronicle to other sites where hurricane sediment records are available: A/ Salt Pond, Massachusetts (Donnelly et al, 2015), B/ South Andros, Bahamas (Wallace et al, 2019), C/ Lighthouse Reef blue hole, Belize (Denommee et al, 2015) (Fig. 9A, B, C).…”
Section: Hurricane Chronicle and Climate Forcingmentioning
confidence: 99%